1975
DOI: 10.1152/ajplegacy.1975.228.5.1376
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical distribution of capillaries in mammalian striated muscle

Abstract: Striated muscles of hindlimb, jaw, or tongue in dogs, cats, rabbits, rats, and guinea pigs were perfused under high pressure with Microfil (a silicone elastomer of viscosity 20 cP approx.) to outline the vascular bed. When the material had set, the muscles were fixed in formalin. Exmination of histological sections, strained by a modified Gomori trichrome method, showed capillaries containing Microfil as well as some, unperfused, filled with red cells. From well-perfused bundles the numbers of capillaries surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(53 citation statements)
references
References 0 publications
5
48
0
Order By: Relevance
“…3A). There were several capillaries surrounding each muscle Wber in a characteristic arrangement for the microvasculature of this tissue [26]. A similar pattern was observed when sections were incubated with anti-CD 31, another marker of endothelial cells (not shown).…”
Section: Immunocytochemistrysupporting
confidence: 73%
“…3A). There were several capillaries surrounding each muscle Wber in a characteristic arrangement for the microvasculature of this tissue [26]. A similar pattern was observed when sections were incubated with anti-CD 31, another marker of endothelial cells (not shown).…”
Section: Immunocytochemistrysupporting
confidence: 73%
“…When comparisons of capillarization are made across studies, it has been suggested that the best measure to use is C/F, since a measure such as capillary density is highly inĀÆuenced by muscle Ā®bre size, which may be aected by shrinkage during histochemical preparation techniques that vary across laboratories. 20 Capillary density and CC/FA are of greater use for assessing capillary supply of Ā®bre area and thus the ability of capillaries to supply oxygen or substrate to muscle, than are C/F and CC. CC/FA is thought to be the best measure of capillary supply to Ā®bres, as C/F and capillary density are global indices of capillarization and yield little information on the capillary supply of individual Ā®bres.…”
Section: Muscle Biopsiesmentioning
confidence: 99%
“…With the variable cap.fibre-1, variations in areas due to the preparation technique are eliminated, and therefore it has been used extensively in the literature to compare results from different studies (see Plyley & Groom, 1975). An increase in cap.fibre-1 reflects formation of new capillaries.…”
Section: Muscle Capillarization and Trainingmentioning
confidence: 99%